A new species of Graphis (Graphidaceae: Lichenized Ascomycota) and a revised key of the genus in Rio Grande do Sul, southern Brazil - Feuerstein, Shirley Cunha; Koch, Natália Mossmann; Lucheta, Fabiane; Vargas, Vera Maria Ferrão; Da Silveira, Rosa Mara Borges (Phytotaxa, 2016)
(A new species of Graphis [Graphidaceae: Lichenized Ascomycota] and a revised key of the genus in Rio Grande do Sul, southern Brazil). In this paper we describe a new species of the lichen genus Graphis, namely G. suzanae Koch & Feuerstein. This species is characterized mainly by lirellae with entire labia, a partially exposed disc with orange pigment in the epithecium, a lateral thalline margin, a laterally carbonized excipulum, a clear hymenium, and transversely septate ascospores measuring 40–44 × 8–10 μm. The chemistry of the species was assessed through TLC analysis. A complete key with G. suzanae and 56 more species of Graphis that where previously recorded to the state of Rio Grande do Sul, southern Brazil, is included.